2015
DOI: 10.15420/ecr.2015.10.01.42
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic Therapy in Heart Failure – Current Approaches

Abstract: The use of diuretics is common in patients with heart failure (HF), to relieve the congestive symptoms of HF. Although they are widely used, there are limited data on their ability to modulate HF-related morbidity and mortality. Diuretic efficacy may be limited by adverse neurohormonal activation and by ‘congestion-like’ symptoms. Diuretics are an extremely useful and varied class of agent for the management of hypervolaemic states. This review summarises the basic features of diuretics, including their mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 49 publications
1
49
0
3
Order By: Relevance
“…However, concerning mechanism and indication, loop diuretics function by enhancing salt and water excretion and are clinically used to maintain euvolaemia or prevent volume expansion. 26 In other words, it makes no significant contribution to alteration of dry body weight, which is used for BMI determination and obesity evaluation. Therefore, despite the above findings, loop diuretics were excluded from our further analysis.…”
Section: Body Mass Index and Beta-blocker Usementioning
confidence: 99%
“…However, concerning mechanism and indication, loop diuretics function by enhancing salt and water excretion and are clinically used to maintain euvolaemia or prevent volume expansion. 26 In other words, it makes no significant contribution to alteration of dry body weight, which is used for BMI determination and obesity evaluation. Therefore, despite the above findings, loop diuretics were excluded from our further analysis.…”
Section: Body Mass Index and Beta-blocker Usementioning
confidence: 99%
“…Clinical data regarding the diuretic effect is controversial because the plasma volume contraction has been shown to level off at~12 weeks of treatment (26). In addition, diuretics have not demonstrated morbidity and mortality benefit in patients with HF, leading researchers to believe the benefit extends beyond natriuresis (27).…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%
“…There is also evidence that epigenetic regulations of NKCC1 may play a role in its effects on the vascular tone [ 97 ]. A study by Lee et al found that the expression of NKCC1 mRNA and protein levels in the aorta and heart tissues are higher in spontaneous hypertensive rats (SHR) than in normotensive rats [ 51 ].…”
Section: Role Of Nkcc In Cardiovascular Diseasementioning
confidence: 99%